Innate immunity ascertained from blood and tracheal aspirates of preterm newborn provides new clues for assessing bronchopulmonary dysplasia - Zaramella, Patrizia; Munari, Fabio; Stocchero, Matteo; Molon, Barbara; Nardo, Daniel; Priante, Elena; Tosato, Francesca; Bonadies, Luca; Viola, Antonella; Baraldi, Eugenio (PloS one, 2019)
The study aimed to establish how granulocytes, monocytes and macrophages contribute to the development of bronchopulmonary dysplasia (BPD). Study A: samples of blood and tracheal aspirates (TAs) collected from preterm newborn infants during the first 3 days of life were investigated by flow cytometry, and testing for white blood cells (WBCs), neutrophils and neutrophil extracellular traps (NETs). Maternal blood samples were also collected. Study B: data from previously-tested samples of TAs collected from preterm newborn infants were re-analyzed in the light of the findings in the new cohort. Study A: 39 preterm newborn infants were studied. A moderate correlation emerged between maternal WBCs and neutrophils and those of their newborn in the first 3 days of life. WBCs and neutrophils correlated in the newborn during the first 8 days of life. Decision rules based on birth weight (BW) and gestational age (GA) can be used to predict bronchopulmonary dysplasia (BPD). Neutrophil levels were lower in the TAs from the newborn with the lowest GAs and BWs. Study B: after removing the effect of GA on BPD development, previously-tested newborn were matched by GA. Monocyte phenotype 1 (Mon1) levels were lower in the blood of newborn with BPD, associated with a higher ratio of Monocyte phenotype 3 (Mon3) to Mon1. Newborn infants from mothers with histological chorioamnionitis (HCA) had lower levels of classically-activated macrophages (M1) and higher levels of alternatively-activated macrophages (M2) in their TAs than newborn infants from healthy mothers. Immune cell behavior in preterm newborn infants was examined in detail. Surprisingly, neutrophil levels were lower in TAs from the newborn with the lowest GA and BW, and no correlation emerged between the neutrophil and NET levels in TAs and the other variables measured. Interestingly, monocyte phenotype seemed to influence the onset of BPD. The rise in the ratio of Mon 3 to Mon 1 could contribute to endothelial dysfunction in BPD.